Kingsman. The golden circle [videorecording (Blu-Ray)] - Vaughn, Matthew, 1971-; Firth, Colin, 1960-; Egerton, Taron, 1989-; Moore, Julianne; Berry, Halle; John, Elton; Tatum, Channing; Bridges, Jeff, 1949-; Millar, Mark; Gibbons, Dave, 1949- (Twentieth Century Fox Home Entertainment, 2017)
When the secret organization headquarters are destroyed and the world is held hostage, their journey leads the agents to the discovery of an allied spy organization in the US called Statesman, dating back to the day they were both founded. In a new adventure that tests their agents' strength and wits to the limit, these two elite secret organizations band together to defeat a ruthless common enemy, in order to save the world, something that's becoming a bit of a habit for Eggsy.